COVID-19 and urban planning: Built environment, health, and well-being in Greek cities before and during the pandemic. (February 2022) - Mouratidis, Kostas; Yiannakou, Athena
Abstract: The coronavirus disease (COVID-19) pandemic has led to dramatic changes in quality of life, bringing to the forefront of the debate the question of planning and design of pandemic-resilient cities. Using quasi-longitudinal survey data (via a social media campaign) and geospatial data from Greek cities, we evaluate changes in health and well-being during COVID-19 compared to the pre-COVID-19 period, and then explore in detail how specific built environment characteristics in Athens and Thessaloniki relate to health and well-being before and during COVID-19. Results suggest that overall health, life satisfaction, happiness, personal relationships satisfaction, leisure satisfaction, satisfaction with income, and satisfaction with vacations all decreased during COVID-19, while anxiety and back pain increased during COVID-19. The role of the urban built environment in health and well-being was found to differ considerably for the COVID-19 period compared to pre-COVID-19. Proximity to large parks, proximity to numerous local facilities, lower neighborhood density, living further from the city center, and living in a larger dwelling were associated with better health and well-being outcomes during COVID-19. Urban planning and relevant policies that cities adopt should carefully focus on mitigating implications for critical issues such as the quest for sustainable urban development and city forms. Highlights: Health and well-being in cities worsened due to the COVID-19 pandemic. The built environment may contribute to COVID-19-related changes in health and well-being. Denser neighborhoods linked to lower well-being during COVID-19. Smaller dwellings linked to worse health outcomes during COVID-19. Implications for cities and urban planning are discussed.